2019
DOI: 10.1101/642389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell RNA-seq in regenerative and fibrotic biomaterial environments defines new macrophage subsets

Abstract: Macrophages play diverse roles in the immune response to infection, cancer, and wound healing where they respond to local environmental signals, yet identification and phenotypic characterization of functional subsets in vivo remains limited. We performed single cell RNA sequencing analysis on differentiated macrophages sorted from a biologic matrix-induced regenerative environment versus a synthetic biomaterial foreign body response (FBR), characterized by TH2/interleukin (IL)-4 and TH17/IL-17, respectively. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For example, polarization with IL4 and IL13, which we used in this study, is considered to promote an M2a phenotype, while polarization with IL10 is considered to promote an M2c phenotype characterized by distinct surface markers like CD163 and increased secretion of numerous matrix-degrading enzymes like matrix metalloprotease (MMP)-7 and -8 [69], suggesting distinct effects on ECM remodeling. Furthermore, transcriptomic studies of macrophages isolated from the in vivo environment suggest that they are difficult to characterize as precisely as macrophage phenotypes studied in vitro [9,19,70]. Therefore, it appears likely that the choice of particular M2 markers used to characterize macrophages strongly affects interpretation, and that large panels of markers should be used to facilitate comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, polarization with IL4 and IL13, which we used in this study, is considered to promote an M2a phenotype, while polarization with IL10 is considered to promote an M2c phenotype characterized by distinct surface markers like CD163 and increased secretion of numerous matrix-degrading enzymes like matrix metalloprotease (MMP)-7 and -8 [69], suggesting distinct effects on ECM remodeling. Furthermore, transcriptomic studies of macrophages isolated from the in vivo environment suggest that they are difficult to characterize as precisely as macrophage phenotypes studied in vitro [9,19,70]. Therefore, it appears likely that the choice of particular M2 markers used to characterize macrophages strongly affects interpretation, and that large panels of markers should be used to facilitate comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
“…While the field continues to evolve, the current state of knowledge is that M1 macrophages initiate healing while M2 macrophages promote healing resolution (for review, see [7,8]). In addition, recent studies employing single cell transcriptomic profiling have shown that macrophages often exist as hybrid phenotypes in vivo, simultaneously expressing markers of both archetypal M1 and M2 phenotypes [9]. Because macrophages switch from M1 to M2 during the course of normal wound healing, the generation of a hybrid M1/M2 phenotype in between these phases is likely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the need for researchers to develop new tools to isolate and explore this population [ 69 ]. Sommerfeld et al [ 70 ] used scRNA-seq to describe the relationship between macrophages isolated from mouse tissue repair models and tissue environmental fibrosis after the use of model biomaterials. They used an unbiased clustering algorithm to reveal the diversity of macrophages, calculated and analyzed the phenotypic characteristics of macrophage clusters, defined phenotypic and functional macrophage populations, identified macrophage surface markers by flow cytometry and immunofluorescence techniques, and identified new CD9hi+IL-36 γ + macrophage populations.…”
Section: Advanced Technology For Studying Macrophage Activationmentioning
confidence: 99%
“…Here, we review recent key findings of the origin of tissue macrophages and how these cells modulate anabolic and catabolic responses in OA, with a particular focus on the constituents of the joint organ system. Furthermore, recent advances in next-generation sequencing technologies and transcriptomic analysis have greatly facilitated our understanding of phenotypic identity and heterogeneity of the macrophage populations 4,5 . Thus, we also summarize the potential contributions of previously unrecognized macrophage subpopulations to OA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%